Preliminary survey of dengue, Zika and chikungunya viruses by nucleic acid test in blood donors in Shenzhen, China - Zheng, Xin; Yan, Xipeng; Xu, Xiaoxuan; Heng, Liu; Cui, Xiujuan; Wu, Linfeng; Li, Ran; Wu, Litao; Chen, Limin; Zeng, Jingfeng (Frontiers in Public Health, 2025)
ObjectiveTo investigate the prevalence of dengue virus (DENV), Zika virus (ZIKV), and chikungunya virus (CHIKV) in blood donors and to preliminarily assess the potential risk of arbovirus transmission through blood transfusion in Shenzhen, China.MethodsThe Nucleic Acid Fully Automatic Mixing Extraction Analysis System from China’s Kehua Biotechnology Company was used to screen for RNAs of DENV, ZIKV, and CHIKV in plasma samples from Mini pools of 8 voluntary blood donors (MP-8). The nucleic acid test results were summarized and analyzed.Results7,520 (75.13%, 7520/10009) and 2,489 (24.87%, 2489/10009) voluntary blood donations were collected from Shenzhen Blood Center and Bao’an District Central Blood Station, respectively, from August 27 to October 18, 2022 for nucleic acid testing of DENV, ZIKV, and CHIKV. Eight donations were mixed to 1 mini-pool (MP-8) and 1,344 test reagents were used for detecting these 1,252 mini-pools. No reactivity was obtained from these 1,252 MP-8 donations. Our results indicated there was an extremely low acute infection rate of DENV, ZIKV, and CHIKV in the surveyed 10,009 blood donations during the summer season in Shenzhen although it is located in the subtropical region of southern China, where Aedes albopictus mosquitoes breed abundantly. This is consistent with previous reports that the positive rate of the nucleic acid testing for DENV, ZIKV, and CHIKV in blood donors is extremely low in China during non-arthropod-borne virus epidemics.ConclusionThe positive rate of acute infections by DENV, ZIKV, and CHIKV in blood donors in arbovirus non-endemic areas in southern China is extremely low, and it is suggested to perform nucleic acid screening only during outbreaks or epidemics. This study not only provides preliminary data on the prevalence and risk assessment of acute infections by DENV, ZIKV, and CHIKV in the blood donor population in Shenzhen, but also equips the technical reserve capacity for emergency screening during unexpected outbreaks of arbovirus epidemics in the region in order to ensure blood safety.